Subthalamic Nucleus Stimulation Impairs Motivation: Implication for Apathy in Parkinson's Disease. Issue 4 (13th January 2020) - Vachez, Yvan; Carcenac, Carole; Magnard, Robin; Kerkerian‐Le Goff, Lydia; Salin, Pascal; Savasta, Marc; Carnicella, Sebastien; Boulet, Sabrina
Abstract: Background: Apathy is one of the most disabling neuropsychiatric symptoms in Parkinson's disease (PD) patients and has a higher prevalence in patients under subthalamic nucleus deep brain stimulation. Indeed, despite its effectiveness for alleviating PD motor symptoms, its neuropsychiatric repercussions have not yet been fully uncovered. Because it can be alleviated by dopaminergic therapies, especially D2 and D3 dopaminergic receptor agonists, the commonest explanation proposed for apathy after subthalamic nucleus deep brain stimulation is a too‐strong reduction in dopaminergic treatments. The objective of this study was to determine whether subthalamic nucleus deep brain stimulation can induce apathetic behaviors, which remains an important matter of concern. We aimed to unambiguously address this question of the motivational effects of chronic subthalamic nucleus deep brain stimulation. Methods: We longitudinally assessed the motivational effects of chronic subthalamic nucleus deep brain stimulation by using innovative wireless microstimulators, allowing continuous stimulation of the subthalamic nucleus in freely moving rats and a pharmacological therapeutic approach. Results: We showed for the first time that subthalamic nucleus deep brain stimulation induces a motivational deficit in naive rats and intensifies those existing in a rodent model of PD neuropsychiatric symptoms. As reported from clinical studies, this loss of motivation was fully reversed by chronic treatment with pramipexole, a D2 and D3 dopaminergic receptor agonist. Conclusions: Taken together, these data provide experimental evidence that chronic subthalamic nucleus deep brain stimulation by itself can induce loss of motivation, reminiscent of apathy, independently of the dopaminergic neurodegenerative process or reduction in dopamine replacement therapy, presumably reflecting a dopaminergic‐driven deficit. Therefore, our data help to clarify and reconcile conflicting clinical observations by highlighting some of the mechanisms of the neuropsychiatric side effects induced by chronic subthalamic nucleus deep brain stimulation. © 2020 International Parkinson and Movement Disorder Society